Novel Functional Analysis for Pathogenic Proteins of Bursaphelenchus xylophilus in Pine Seed Embryos Using a Virus Vector - Kirino, Haru; Konagaya, Ken-ichi; Shinya, Ryoji (Frontiers in Plant Science, 2022)
Pine wilt disease (PWD), which is caused by the pine wood nematode Bursaphelenchus xylophilus, is among the most serious tree diseases worldwide. PWD is thought to be initiated by sequential excessive hypersensitive responses to B. xylophilus. Previous studies have reported candidate pathogenic molecules inducing hypersensitive responses in pine trees susceptible to B. xylophilus. The functions of some of these molecules have been analyzed in model plants using transient overexpression; however, whether they can induce hypersensitive responses in natural host pines remains unclear due to the lack of a suitable functional analysis method. In this study, we established a novel functional analysis method for susceptible black pine (Pinus thunbergii) seed embryos using transient overexpression by the Apple latent spherical virus (ALSV) vector, and investigated five secreted proteins of B. xylophilus causing cell death in tobacco to determine whether they induce hypersensitive responses in pine. We found that three of five molecules induced significantly higher expression in pathogenesis-related (PR) genes (P < 0.05), indicating hypersensitive response in pine seed embryos compared with mock and green fluorescence protein controls. This result suggests that tobacco-based screening may detect false positives. This study is the first to analyze the function of pathogenic candidate molecules of B. xylophilus in natural host pines using exogeneous gene expression, which is anticipated to be a powerful tool for investigating the PWD mechanism.